The impact of inflation on economic security: an analysis based on the experience of Uzbekistan and South Korea - Gofurova Lola (THE INNOVATION ECONOMY, 2026)
This article provides a detailed analysis of the impact of inflation on economic security, using Uzbekistan and South Korea as case studies. The study examines how inflation affects the national economy, real incomes of the population, investment environment, fiscal policy, and macroeconomic stability based on statistical data and recent economic indicators. The article also analyzes effective strategies, policy measures, and institutional mechanisms for controlling and reducing inflation. Practical recommendations for Uzbekistan are presented, aimed at strengthening economic security, improving the welfare of citizens, and enhancing investor confidence. The results of the study demonstrate a direct correlation between the level of inflation and economic security, highlighting the importance of national policy and economic management in effectively managing this process.